Mortgage design, repayment schedules, and household borrowing - Claes Bäckman; Patrick Moran; Peter van Santen (Leibniz Institute for Financial Research SAFE, 2024)
How does the design of debt repayment schedules affect household borrowing? To answer this question, we exploit a Swedish policy reform that eliminated interest-only mortgages for loan-to-value ratios above 50%. We document substantial bunching at the threshold, leading to 5% lower borrowing. Wealthy borrowers drive the results, challenging credit constraints as the primary explanation. We develop a model to evaluate the mechanisms driving household behavior and find that much of the effect comes from households experiencing ongoing flow disutility to amortization payments. Our results indicate that mortgage contracts with low initial payments substantially increase household borrowing and lifetime interest costs.
Keywords: G51; G21; E21; E6; 330; Mortgage design; Amortization payments; Macroprudential policy; Bunching